(3JMQjQ GdeLSWis - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s; (3HWdejhS GdMcjes ((3eMeO MSjf Hf GdcGXe GdbRhjfi GdehShi s)
(3ChdgG (B:s
(3CMeO Gddg eHOC cd eHOC , hZGjI cd ZGjI hHYO , abO cfJ HQgI ef GdReGf , YGRekG Ydi Cf CMQQ dfaSi , hdSGFQ WdHg GdYde ef GdENhGf , cJGH GdeLSWi , GdefShH Edi HWdjehS GdbdhPi s
(3BNQgG (B:s
(3aEPG CJeefG LeY eG jZfi GdLGO SDGd ef hLhO eG jMJGL Edjg Edi hLhOg , hJUMjM eG jMJGL Edi JUMjMg adfNJe GdcJGH , hCbhd hEPG habfi Gddg JYGdi GGjVkG Ydi JeGe eG aUdJg hEfLGR eG hYOJg Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3HgG LOGhd hCTcGds
(3HChdgG agQS ddehVhYGJs
(3fSNI QGHYI s
(3jJab ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa ai HYV GdCdaGX s
(3fbdgG GdfGSN ef fSNI fbdJ ef fSNI GdeDda cJHgG HNWg SfI (B644(3g` s
Keywords: (3Gdadcs